If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + 6) + -1(2 + 6y) = 9 Reorder the terms: (6 + 7y) + -1(2 + 6y) = 9 Remove parenthesis around (6 + 7y) 6 + 7y + -1(2 + 6y) = 9 6 + 7y + (2 * -1 + 6y * -1) = 9 6 + 7y + (-2 + -6y) = 9 Reorder the terms: 6 + -2 + 7y + -6y = 9 Combine like terms: 6 + -2 = 4 4 + 7y + -6y = 9 Combine like terms: 7y + -6y = 1y 4 + 1y = 9 Solving 4 + 1y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1y = 9 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = 9 + -4 1y = 9 + -4 Combine like terms: 9 + -4 = 5 1y = 5 Divide each side by '1'. y = 5 Simplifying y = 5
| (x-1)(x-4)(x-6)+(-2)(-5)(-3)+(-3)(-2)(-5)-(-2)(-2)(x-6)-(x-1)(-5)(-5)-(-3)(x-4)(-3)=0 | | pe=9c | | 4y+4y=7y-5 | | [5-2(5-4)]= | | (w+23)+(4w+7)=18 | | 6x+2+4x+9=9x+3 | | 4y=7-5x | | -2x-(7x+1)= | | x^3+x^2-3x=0 | | 20+2x=4x | | 5a^2+34a+45=0 | | d-0.15d+10=180 | | 19-30(x+2)=-20(1-x) | | 19-30(x+2)=20(1-x) | | 3m+4n-6(4m-4n)= | | 3.5m-3.4-4.5m=9.5-1m-12.9 | | 3(3x+4)-2x-9=5 | | x^3-11x^2-4x+1=0 | | x=0.4(456-0.6(456-x)) | | 4x+29=6x+7 | | -8m^3+10m=0 | | 4(2x^2-3x+5)= | | 6-3x=-3x-6 | | 4(2m-2n)+3(7m+n)= | | 30+10x=6x+10 | | x=0.4(4.56-0.65(4.65-x)) | | .5(4r+2)=0 | | 2w^3+3w^2-10w-15= | | 5(x)=3x^2-3x | | 7=-4x+2 | | 4.6q-5.9-5.5q=-1.9q-2.4 | | 3x-2=-6 |